Respuesta :

(3a - 4)^2 =
(3a - 4)(3a - 4) =
3a(3a - 4) - 4(3a - 4) =
9a^2 - 12a - 12a + 16 =
9a^2 - 24a + 16 <== I am not getting what ur teacher got

is the problem written correctly ?
Because (3a - 3)^2 = 9a^2 - 18a + 9
rw22
Well (3a - 4)^2 is equivalent to (3a - 4) * (3a - 4)
How I would solve that is by firstly multiplying (3a - 4) by 3a (first part of second bracket) then adding that to (3a - 4) * - 4 (second part of second bracket)

That would equal
(9a^2 - 12a) + (-12a + 16)
= 9a^2 - 12a - 12a + 16
= 9a^2 - 24a +16

Sorry if my answer is rubbish
ACCESS MORE